2014
DOI: 10.15256/joc.2014.4.31
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Adults with Multimorbidity: A Qualitative Study

Abstract: BackgroundFindings from several countries indicate that the prevalence of multimorbidity is very high among clients of primary healthcare. A deeper understanding of patients’ experiences from their own perspective can greatly enrich any intervention to help them live as well as possible with multimorbidity.ObjectiveTo describe the fundamental structure of adults’ experience with multimorbidity.DesignA phenomenological study was undertaken to describe the experiences of 11 adults with multimorbidity. These adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 21 publications
7
68
0
Order By: Relevance
“…6,8 Despite this, health care delivery remains focused on the management of single diseases, creating major challenges for both patients and clinicians. 2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Despite this, health care delivery remains focused on the management of single diseases, creating major challenges for both patients and clinicians. 2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage.…”
Section: Introductionmentioning
confidence: 99%
“…As the previous discussion has outlined, individuals must make substantial investments in the day-to-day management of a chronic illness, but for those with multiple conditions the challenges of living with chronic illness are amplified (16,111,(191)(192)(193)(194). Multimorbidity, "the most common chronic condition experienced by adults", places significant demands on individuals, clinicians and the health system (25).…”
Section: Multiple Conditions: the Patient Experiencementioning
confidence: 99%
“…Such changes are often difficult to implement as individuals with multiple chronic conditions, experience greater disability and physical impairment than is generally associated with one condition (73,79,93,(111)(112)(113)192,193,212).…”
Section: Lifestyle Change Burdenmentioning
confidence: 99%
See 2 more Smart Citations